A new threat for the endangered frog Atelognathus reverberii (Anura: Batrachylidae) in Argentinean Patagonia - Akmentins, Mauricio Sebastián (2015)
Atelognathus reverberii (Cei, 1969) is an endemic terrestrial frog that inhabits volcanic clay lagoons (mostly semi-permanent or temporary). These lagoons are scattered throughout the desertic Somuncura Plateau of Argentinean Patagonia (Cei 1969, Martinazzo et al. 2011). This frog species was listed as Endangered in the IUCN’s red list (IUCN 2014) and as Vulnerable in the last categorization of Argentinean amphibian fauna (Vaira et al. 2012).